PERMUKIMAN TRADISIONAL DI KAWASAN LANSKAP PANTAI DI SENDIKI, DESA TAMBAKREJO KECAMATAN SUMBERMANJING WETAN KABUPATEN MALANG - Irawan Setyabudi; Petrus Paulus Pain Pati (BUANA SAINS, 2019)
Traditional settlements are places that still hold customary and cultural values related to beliefs or religion that are specific or unique to a particular society. In each region of Nusantara there are various cultures, and in it there are traditional settlements as identities. This research is located in the Sendiki beach area which is a tourist attraction in the southern Malang district, precisely in the village of Tambakrejo. The problem is the diminishing public awareness in preserving the existence of settlement forms because of the current of modernization. The unique settlement pattern model in the village of Tambakrejo lined up along the road following the traditional settlement pattern of Tanean Lanjeng, because the settlements were dominated by Madura race. On the other hand because it is located in East Java, the formation of his house was also adapted to the building form of joglo. Another problem is the low public awareness in maintaining environmental quality which impacts the degradation of ecosystem quality. The aims of this research include identifying the architectural forms of houses, landscapes and traditional settlements in the village of Tambakrejo, as an effort to preserve them. The research method was conducted qualitatively by analyzing the data using Focus Group Discussion (FGD). The research thinking is adapted to the ideas of Rapoport. The stages of research start from the identification of physical, biophysical, socio-cultural and economic aspects, to the description of analysis and synthesis in settlement patterns and traditional homes. The results obtained in the form of a description of traditional settlement patterns, the formation of residential architecture and landscape patterns of settlements. The conclusions of this study include documentation of traditional architecture, landscapes and settlements as knowledge to respect the natural environment and culture of the people living.